2012
DOI: 10.4236/jasmi.2012.23027
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Removal of Antimony (III) Using Modified Montmorillonite: A Study on Sorption Kinetics

Abstract: The adsorptive removal of antimony (III) has been successfully obtained on montmorillonite (MMT) and modified MMT from synthetic solution. The adsorption behavior of the modified and unmodified MMT has been investigated as a function of initial concentration of metal ion in the solution, pH of the solution and contact time using a batch extraction process. The optimized process can be applied for the adsorption, detection and estimation of antimony from 0.006 µg/ml (6.0 ppb) to 100.00 µg/ml (100.0 ppm) in aque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
(26 reference statements)
0
4
0
1
Order By: Relevance
“…Tiek izmantoti arī dažādi minerāli, piemēram, adsorbcijai var izmantot kaolinītu [13], gibsītu [14], diatomītu doi: 10.7250/msac.2013.027 102 [15], montmorilonītu, kas apstrādāts ar virsmaktīvām vielām [16], kā arī gētītu [17].…”
Section: Ievadsunclassified
“…Tiek izmantoti arī dažādi minerāli, piemēram, adsorbcijai var izmantot kaolinītu [13], gibsītu [14], diatomītu doi: 10.7250/msac.2013.027 102 [15], montmorilonītu, kas apstrādāts ar virsmaktīvām vielām [16], kā arī gētītu [17].…”
Section: Ievadsunclassified
“…Factors such as choice of clay minerals and cationic surfactants as well as the amounts of organic cations chosen might affect the efficacy and adsorption performance of organ minerals [23]. Anjum and Datta [28] studied the adsorptive removal of antimony (III) on modified clays at low concentration range (6μg/L to 100mg/L) and showed that montmorillonites modified with methylpyridinium chloride and cetyl trimethylammonium bromide are efficient adsorbents for the removal of low concentrations of antimonite. Bagherifam, et al [23] studied the effect of hexadecyl pyridinium chloride modified montmorillonite (HDPy+-M) and hexadecyl pyridinium bromide modified zeolite (HDPy+-Z) on Sb(III) uptake from solutions containing 0.5-2.5 mM antimonite, and their result was quite encouraging.…”
Section: Introductionmentioning
confidence: 99%
“…Molybdenum drioxide (MoO 3) / molybdenum disulfide (MoS 2 ) composite is a core-shell nanorod with high surface properties [ 3 5 ]. Molybdenum disulfide (MoS 2 ) contained some active edge regions and exhibits crystallite properties [ 6 ].…”
Section: Introductionmentioning
confidence: 99%